New species and new records of Deliphrosoma Reitter, 1909 (Coleoptera: Staphylinidae: Omaliinae) from Iran with note on the taxonomic status of Geodromicus libanicus Coiffait, 1985 - A.V. Shavrin (Кавказский энтомологический бюллетень, 2011)
Deliphrosoma frischi sp. n. from Esfahan province of Iran is described and illustrated. New records of D. bakhtiyariense Zerche, 1991, for Esfahan province and D. morvani (Jarrige, 1971) for Alborz province are provided. One new synonymy is established: D. libanicum (Fauvel, 1875) = Geodromicus libanicus Coiffait, 1985 syn. n.